Sour sweet harvest - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
After Fiji s sugar crushing season ended in January 2001, it turned out that the country only produced 341,000 tonnes of sugar about 25% less than in 2000. A late start to the season because of last year s coup, wet weather and an over-supply of...